Constitutive activity of the inhibitory G protein pathway mediated by non-visual opsin Opn7b reduces cFos activity in stress and fear circuits and modulates avoidance behavior - Böke, Hanna; Schulte, Hannah; Worm, Maria; Bihorac, Julia; Mücher, Brix; Hadamitzky, Martin; Siveke, Ida; Herlitze, Stefan; Spoida, Katharina (Frontiers in Behavioral Neuroscience, 2025)
Constitutive activity of G protein-coupled receptors (GPCRs) plays an important role in brain function and disease including neurodegenerative and psychiatric disorders. The non-visual opsin Opn7b is a constitutively active Gi/o coupled GPCR which has been used to synchronize neuronal networks. Here we show that expression of Opn7b in the bed nucleus of the stria terminalis and the ventral tegmental area, two interconnected brain areas involved in modulating fear and stress responses, reduces the number of cFos positive neurons and modulates avoidance behavior in mice. Thus, by constitutively activating the Gi/o pathway Opn7b can be used as a tool to reduce cFos expression and to link cFos-expressing neurons to network- and pathway-specific behavior.